The Relationship between Human Embryo Parameters and De Novo Chromosomal Abnormalities in Preimplantation Genetic Testing Cycles - Yanli Liu; Junhan Shen; Rujing Yang; Yuchao Zhang; Liting Jia; Yichun Guan (International Journal of Endocrinology)
Research Question. What is the incidence of de novo chromosome abnormalities (>4 Mb), and are they related to embryo parameters in preimplantation genetic testing for chromosome structural rearrangement (PGT-SR) cycles and preimplantation genetic testing for aneuploidy (PGT-A) cycles? Design. In total, 456 PGT cycles, including 283 PGT-SR cycles and 173 PGT-A cycles, were assessed through comprehensive chromosome screening (CCS) from January 2017 to June 2020 at the Department of Reproductive Medicine of the Third Affiliated Hospital of Zhengzhou University. Trophectoderm (TE) biopsies were sequenced using next-generation sequencing (NGS). The incidence of de novo chromosome abnormalities was calculated, and the relationships between de novo chromosome abnormality rates and maternal age, number of oocytes retrieved, and parameters of cleavage-stage embryos and blastocyst-stage embryos were investigated. Results. The incidence of de novo chromosome abnormalities was 28.0% (318/1,135) in the PGT-SR cycles and 36.3% (214/590) in the PGT-A cycles, which increased with maternal age in both PGT-SR cycles (P = 0.018) and PGT-A cycles (P < 0.001). The incidence of de novo chromosome abnormalities was related to TE grade (P < 0.001), internal cell mass grade (P = 0.002), and development speed (day 5 vs. day 7: P < 0.001) of blastocyst-stage embryos. The incidence of de novo chromosomal abnormalities was irrelevant to the number of oocytes retrieved and the parameters of the embryo at the cleavage stage. Conclusion. Blastocysts with higher morphology scores and faster progression had a lower incidence of de novo chromosome abnormalities, especially complex chromosome abnormalities. De novo chromosome abnormalities may negatively affect the morphological grading of blastocysts. Our findings will provide valuable information to the fertility doctor for embryo selection in non-PGT cycles.